Food safety perceptions and practices among smallholder pork value chain actors in Hung Yen Province, Vietnam - Dang-Xuan S. (2017)
Copyright ©, International Association for Food Protection. Pork safety is an important public health concern in Vietnam and is a shared responsibility among many actors along the pork value chain. We examined the knowledge, perceptions, and practices regarding food safety, disease, and health risk among selected pork value chain actors (slaughterhouse owners and workers, people living around slaughterhouses, pork sellers, consumers, and veterinary and public health staff) in three districts in Hung Yen Province, Vietnam. We randomly selected 52 pork value chain actors to be surveyed through questionnaires, observation checklists, key informant interviews, and focus group discussions. Most slaughterhouse workers acquired knowledge and experience of food safety through "learning by doing" rather than from training by a veterinary or public health professional. Both slaughterhouse worker and pork seller groups had some accurate perceptions about pig diseases and foodborne diseases; however, misperceptions of risk and, especially, of zoonoses were present. Furthermore, while workers and sellers often use cloths to dry the meat and clean equipment, they did not think this was a risk for meat contamination. Moreover, when sellers wear protective equipment, such as gloves, masks, or hats, consumers perceive that the sellers may have health issues they are trying to conceal and so consumers avoid buying from them. The perceived freshness of pork, along with trust in the seller and in the pork production process, were strong indicators of consumer preference. And yet, pork value chain actors tend to trust their own individual food safety practices more, rather than the practices of other actors along the chain. Veterinary and public health staff emphasized the gap between regulations and food safety practices. Education and training on food safety risks and proper handling are priorities, along with integrated and intensive efforts to improve food safety among pork value chain actors.